Private politics and public regulation - Georgy Egorov; Bård Harstad (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2015)
Private politics are often introduced by market participants in the absence of public regulation. But when is private politics enough, efficient, or better than administratively costly public regulation? We present a novel framework in which we can study the interaction between regulation, self-regulation by the firm, and boycotts by the activists in a dynamic game. Our main results are the following. (i) The possibility to self-regulate saves on administrative costs, it therefore also leads to delays. (ii) The possibility to self-regulate benefits activists but harms the firm without the public regulator in place, the reverse is true with the regulator being present in the game. (iii) Without the public regulator, a boycott raises the likelihood of self-regulation, whereas if the regulator is present, it raises the likelihood of public regulation. (iv) Activism is a strategic complement to self-regulation, but a strategic substitute to public regulation. (v) In addition, the analysis generates a rich set of testable predictions regarding the regulatory outcomes and the duration of boycotts.
Keywords: D78; L31; L51; 330; private politics; boycotts; war of attrition; activism; regulation; self-regulation; corporate social responsibility (CSR)